An Ethnographic Exploration of the Lived Experiences with Gynecologic Cancers - Naser Aldeen, Norma (AUC Knowledge Fountain, 2026)
Abstract This thesis stays close to conversations with nine women who spoke about living with and through gynecologic cancers, from moments of finding out, through treatment, and into what follows. These encounters unfolded primarily through digitally mediated exchanges across Baalbek, Beirut, and other translocal settings shaped by distance and movement. Rather than approaching illness as a bounded biomedical event, this thesis attends to how gynecologic cancer is narrated as something that lingers—pressing into everyday life through bodily sensations, altered rhythms, and ongoing recalibrations of care, responsibility, and what remains possible. Across these encounters, care rarely appears as a stable system or completed intervention. Instead, it emerges contingently—assembled through shifting relations, material constraints, and moments of improvisation that are often provisional—within healthcare landscapes shaped by privatization, selective regional investment, and political and institutional withdrawal rooted in longer political histories of abandonment and uneven governance. The interlocutors’ accounts move through fragmented medical worlds shaped by delayed access, financial strain, and uneven support. They remain close to the everyday labor of navigating these conditions within gendered social worlds, where responsibility for care is often hierarchically distributed. The long “after” of illness surfaces through persistent fatigue, pain, and bodily change; unsettled negotiations of intimacy and sexuality; and the ordinary work of living with uncertainty, without presuming recovery, resolution, or linear progress. Within these conditions, the interlocutors describe negotiating, redirecting, and at times refusing the normative and temporal terms through which care is made available. This thesis approaches ethnography as a practice of listening with the interlocutors’ narratives as situated forms of knowledge, attentive to pauses, gestures, silences, and returns through which illness is narrated or reworked, particularly within digitally mediated encounters shaped by interruption and ongoing relational reorientation. In doing so, this thesis foregrounds lived experience as a mode of knowing, without reducing it to illustrative or extractive data. Staying with these modes of listening, this thesis attends to what often slips to the margins of clinical, humanitarian, and survivorship framings: the unfinished and relational ways care is lived long after formal treatment recedes. Rather than offering a representative account or unified narrative, this thesis holds to partiality, fragmentation, and ongoingness. What unfolds across the chapters are not conclusions about illness or care, but moments of hesitation, recalibration, and continuance through which the interlocutors describe living the long after of gynecologic cancer—where care remains unfinished, continually negotiated through hierarchized medical and social worlds that actively differentially value lives and shape the conditions of continuance under uneven political and economic arrangements. Key words: Gynecologic Cancer; Cancer Survivorship; Unfinished Care; Medical Anthropology; Relational Subjectivity; Digital Ethnography; Political Economy of Care; Healthcare Privatization; Organized Abandonment; Lebanon